TECHNIKI OBRAZOWANIAAssessment of myocardial viability in cardiovascular magnetic resonance prior to revascularization procedure in a patient with left ventricle myocardial thinning. A case report - Biełka, Agnieszka; Miszalski-Jamka, Tomasz; Głowacki, Jan; Jarski, Piotr; Kalarus, Zbigniew (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2009)
Delayed contrast-enhanced magnetic resonance imaging (DE-MRI) with use of gadolinium-based contrast enables assessment of postinfarction scar size in the left ventricle wall. It is known as transmural extent of hyperenhancement (TEI) and is the percentage ratio of scar thickness to total end diastolic wall thickness in a given segment. TEI correlates with probability of improvement in contractility after a revascularization procedure. The greatest chance for improvement is shown by myocardial segments with TEI less than 50%, and it is very low for segments with TEI over 75%. The presented case confirmed the usefulness of TEI assessment in DE-MRI before a revascularization procedure in a patient after myocardial infarction with regional myocardial thinning. DE-MRI should be considered as one of the methods of viability assessment in patients after myocardial infarction planned for revascularization.